Criminal Trials Through E-Court During The Covid-19 Period as A Form of the Principle of Fast, Simple and Low-Cost Justice - Herlina Manullang (Journal of Social Research, 2022)
Background: Spread corona virus disesea (Covid-19) in Indonesia has changed the implementation of the trial system, especially the trial of criminal cases using applications e-court. The maximum use of the e-court system has been implemented in line with the issuance of Supreme Court Regulation No. 1 of 2019 concerning Procedures for Electronic Trials (hereinafter referred to as Perma No. 1 of 2019). Objective: to guarantee the three basic values of legal objectives, namely justice, expediency and legal certainty. In addition, the application of the principles of simplicity, speed, and low cost in the judicial process can be interpreted broadly, including aspects of regulation, institutional and judicial processes. Methods: The approach method used in this paper is a statutory approach (statute approach) and conceptual approac. Results: The embodiment of criminal trials through e-courts during the covid-19 period has become a solution for the implementation of the principles of fast, simple and low-cost justice, while still upholding the principles of justice solus populi suprema lex esto. Conslusion: The existence of Perma No. 4 The year 2020 is an effort to reform the judicial system in Indonesia which is more modern and an effort to reform the Criminal Procedure Code in Indonesia, especially during the covid-19 period. Whereas the e-court trial has similarities to the Criminal Procedure Code, but still has differences that cannot be ignored.